2017
DOI: 10.1021/acsnano.7b05170
|View full text |Cite
|
Sign up to set email alerts
|

Organic Solvent-Free Fabrication of Durable and Multifunctional Superhydrophobic Paper from Waterborne Fluorinated Cellulose Nanofiber Building Blocks

Abstract: In view of a great demand for paper-based technologies, nonwettable fibrous substrates with excellent durability have drawn much attention in recent years. In this context, the use of cellulose nanofibers (CNFs), the smallest unit of cellulosic substrates (5-20 nm wide and 500 nm to several microns in length), to design waterproof paper can be an economical and smart approach. In this study, an eco-friendly and facile methodology to develop a multifunctional waterproof paper via the fabrication of fluoroalkyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(116 citation statements)
references
References 64 publications
3
113
0
Order By: Relevance
“…Owing to the competition between transparency and surface roughness, realizing high transparency of most superamphiphobic coatings, especially water‐based superamphiphobic coatings, is difficult. [ 39 ] Figure 1d reveals that the transmittance of the pristine glass and the WSC‐coated glass is similar, and the coated glass is even antireflective at wavelengths ranging from 440 to 800 nm. In addition, the clear university logos beneath the coated glass and spherical droplets of water, olive oil, and hexadecane on the coated glass demonstrate that the coated glass is simultaneously transparent and superamphiphobic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the competition between transparency and surface roughness, realizing high transparency of most superamphiphobic coatings, especially water‐based superamphiphobic coatings, is difficult. [ 39 ] Figure 1d reveals that the transmittance of the pristine glass and the WSC‐coated glass is similar, and the coated glass is even antireflective at wavelengths ranging from 440 to 800 nm. In addition, the clear university logos beneath the coated glass and spherical droplets of water, olive oil, and hexadecane on the coated glass demonstrate that the coated glass is simultaneously transparent and superamphiphobic.…”
Section: Resultsmentioning
confidence: 99%
“…A few strategies have been reported about preparing water‐based superhydrophobic coatings and even water‐based superamphiphobic coatings. [ 37–44 ] The focus of the present studies is on the preparation of these coatings. However, high performances of water‐based superhydrophobic coatings are neglected which are the key factors in wide, long‐term, and efficient application, due to the difficulty in achieving them.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that cellulose requires some specific surface treatments in order to obtain a polymer composite of a sufficient performance. Fortunately, there are many known examples of chemical modifications that are carried out in neat conditions and in solvent-free environments, e.g., acetylation [41,42], carboxylation [43,44], and fluorination [45]. Moreover, cellulose is not only being modified in mild conditions; other treatments include lignocellulose acetylation [46] and lignin acetylation [47].…”
Section: Of 18mentioning
confidence: 99%
“…For these reasons, researchers have attempted to design a superhydrophobic coating that is self-cleaning, dust-proof, moisture-proof, and anticorrosion [2][3][4][5]. Examples of such studies include Ogihara et al [6], who reported that superhydrophobic coatings can be deposited on paper by spraying alcohol suspensions of SiO 2 nanoparticles; Baidya et al [7] described a simplistic methodology to develop a superhydrophobic paper via manufacture of fluoroalkyl functionalized cellulose nanofibers (CNFs); Shi et al [8] prepared a superhydrophobic nanocomposite coating using hydrophobic silica nanoparticles as a filter and polyvinylidene fluoride (PVDF) as a film-forming material, which was applied to the paper's surface through a simple, one-step spray dispersion method; Wang et al [9] manufactured a superhydrophobic paper by coating it with silica sol using tetraethylorthosilicate (TEOS) and trimethylethoxysilane (TMES) as a precursor and coprecursor, respectively. However, the superhydrophobic coatings prepared by the above methods are lacking resistance to oily substances and thus do not have a selfcleaning effect [10].…”
Section: Introductionmentioning
confidence: 99%